The Effect of Drug Availability and the Quality of Pharmaceutical Services on Patient Satisfaction at Bulan Mulya Primary Clinic (Inpatient), Perawang - Zulfia Aulia Putri; Riska wani Eka Putri; Norwetin Situmorang (Jurnal EduHealth, 2026)
Drug availability and the quality of pharmaceutical services are important factors influencing patient satisfaction in healthcare facilities. This study aimed to analyze the effect of drug availability and pharmaceutical service quality on patient satisfaction at Bulan Mulya Perawang Primary Clinic (Inpatient). This research employed a quantitative method with a cross-sectional design. Data were collected using structured questionnaires distributed to 50 patients who had received pharmaceutical services at the clinic. The data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis with SPSS.The results showed that all research instruments were valid and reliable. Classical assumption tests indicated that the data were normally distributed and free from multicollinearity and heteroscedasticity. Multiple linear regression analysis revealed that drug availability and pharmaceutical service quality had a positive and significant effect on patient satisfaction, both partially and simultaneously. The correlation coefficient indicated a moderately strong relationship between the independent variables and patient satisfaction (R = 0.664). The coefficient of determination (R²) was 0.425, indicating that 42.5% of patient satisfaction was influenced by drug availability and pharmaceutical service quality, while the remaining 57.5% was affected by other factors not examined in this study. These findings highlight the importance of ensuring adequate drug availability and improving pharmaceutical service quality to enhance patient satisfaction